1998
DOI: 10.1021/jm9703754
|View full text |Cite
|
Sign up to set email alerts
|

Dihydropyrancarboxamides Related to Zanamivir:  A New Series of Inhibitors of Influenza Virus Sialidases. 2. Crystallographic and Molecular Modeling Study of Complexes of 4-Amino-4H-pyran-6-carboxamides and Sialidase from Influenza Virus Types A and B

Abstract: The first paper in this series (see previous article) described structure-activity studies of carboxamide analogues of zanamivir binding to influenza virus sialidase types A and B and showed that inhibitory activity of these compounds was much greater against influenza A enzyme. To understand the large differences in affinities, a number of protein-ligand complexes have been investigated using crystallography and molecular dynamics. The crystallographic studies show that the binding of ligands containing terti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
152
1
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(159 citation statements)
references
References 23 publications
5
152
1
1
Order By: Relevance
“…We confirmed that this substitution led to a low level of virus resistance to zanamivir (8-fold) and a moderate level of resistance to RWJ-270201 (27-fold), despite the apparent need for reorientation for the interaction of RWJ-270201. The reorientation of the side chain of Glu276 could be energetically less favorable in influenza B virus NAs than in influenza A virus NAs, because the region surrounding Glu276 is hydrophobic in influenza B viruses and hydrophilic in influenza A viruses (23). Differences in binding of inhibitors to influenza A and B virus NAs have been reported previously (1,23).…”
Section: Discussionmentioning
confidence: 86%
“…We confirmed that this substitution led to a low level of virus resistance to zanamivir (8-fold) and a moderate level of resistance to RWJ-270201 (27-fold), despite the apparent need for reorientation for the interaction of RWJ-270201. The reorientation of the side chain of Glu276 could be energetically less favorable in influenza B virus NAs than in influenza A virus NAs, because the region surrounding Glu276 is hydrophobic in influenza B viruses and hydrophilic in influenza A viruses (23). Differences in binding of inhibitors to influenza A and B virus NAs have been reported previously (1,23).…”
Section: Discussionmentioning
confidence: 86%
“…In the case of influenza B neuraminidase, it has been reported that the rearrangement of Glu 276 is energetically less favorable (1,14). Although both oseltamivir carboxylate and RWJ-270201 have hydrophobic groups.…”
Section: Discussionmentioning
confidence: 99%
“…The affinity of a compound such as oseltamivir carboxylate, which depends on this movement for optimal binding (19), is expected to be significantly affected by this mutation in N9. Structure-activity relationship data for zanamivir suggest that E276 is not required to move for high potency in N1, N2, N9, and B enzymes, so the fold resistance of zanamivir is minimal for K292 mutants (12,21,23,32,33).…”
Section: Discussionmentioning
confidence: 99%